Emerging Role for Acyl-CoA Binding Domain Containing 3 at Membrane Contact Sites During Viral Infection - Lu, Yue; Song, Siqi; Zhang, Leiliang (Frontiers in Microbiology, 2020)
Acyl-coenzyme A binding domain containing 3 (ACBD3) is a multifunctional protein residing in the Golgi apparatus and is involved in several signaling pathways. The current knowledge on ACBD3 has been extended to virology. ACBD3 has recently emerged as a key factor subverted by viruses, including kobuvirus, enterovirus, and hepatitis C virus. The ACBD3-PI4KB complex is critical for the role of ACBD3 in viral replication. In most cases, ACBD3 plays a positive role in viral infection. ACBD3 associates with viral 3A proteins from a variety of Picornaviridae family members at membrane contact sites (MCSs), which are used by diverse viruses to ensure lipid transfer to replication organelles (ROs). In this review, we discuss the mechanisms underlying the involvement of ACBD3 in viral infection at MCSs. Our review will highlight the current research and reveal potential avenues for future research.